Multimodalidad y Patrimonio Cultural Inmaterial (PCI) - Asiáin Ansorena, Alfredo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2016)
Given the need to approach the recording, study and transmission of multimodality and multisensoriality of ICH, this paper proposes a reflection on the most appropriate methodology and technological means for its documentation, study and transmission. Given the complexity of annotating, analyzing and researching the manifestations of the Intangible Cultural Heritage, a first approach to the postulates of multimodal discourse analysis (AMD) is made. This emerging paradigm in the field of discourse studies extends linguistic analysis to that of language in combination with other modes of communication (O’Halloran, 2004 & 2012). This paper endorses a sensory analysis of the ICH and concludes that it should be studied as multimodal hypertexts. This new genre requires, in turn, multimodal literacy or multimodal learning within new literacies (Jewitt, 2009; Cassany, 2012; Street et al. 2009).